Warung Kopi sebagai Ruang Publik untuk Membangun Harmoni Masyarakat Multikultural - Pipit Widiatmaka; M. Fadhil Yarda Gafallo; Taufik Akbar; Adiansyah Adiansyah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Inter-ethnic conflicts often occur in West Kalimantan, especially in Pontianak City, especially between Dayak, Chinese, and Malay ethnicities. Therefore, to build harmony in life between ethnicities, public spaces are needed that are accessed by various groups. Coffee shops are one of the potential public spaces to build harmony between ethnic groups. This article aims to determine the existence of coffee shops as public spaces in Kota Pontianak and the role of coffee shops as a space to build harmony in Pontianak City. This article publishes the results of research that uses qualitative approaches with phenomenological methods, data collection using interviews, observation, observation techniques, and documentation. Data analysis uses an interactive analysis model. The research found that coffee rafting in Pontianak City becomes a public space that contains democratic, responsive, and meaningful values so that people from various ethnic and cultural backgrounds visit coffee shops to rest, discuss business affairs, do tasks, have meetings, and so on. People who visit coffee shops come from various ethnicities (Malay, Dayak, Chinese, Bugis, Javanese, and Madurese). Through the coffee shop, they meet to talk about various things, so that familiarity is well- built  and  strengthens  social  integration.  Besides  being  able  to  build  a  harmonious  inter-ethnic  life, the existence of coffee shops can also increase the regional original income (PAD) of Pontianak City and absorb labor.